Urgent and emergent radiotherapy for hematologic malignancies of the central nervous system: a review of the literature and practical approach - Tringale, Kathryn R.; Imber, Brandon S.; Cederquist, Gustav Y.; Yahalom, Joachim; Moore, Zachary R.; Hoppe, Richard T.; Binkley, Michael S.; Ross, Jason B.; Wijetunga, N. Ari; Sanghvi, Parag; Casey, Dana L.; Hiniker, Susan M. (Frontiers in Oncology, 2025)
IntroductionHematologic malignancies, including leukemias, lymphomas, and myeloma, can involve the central nervous system (CNS) at the time of diagnosis or later in relapse. CNS involvement can lead to acute neurologic symptoms or signs that need prompt evaluation and treatment. Radiotherapy (RT) can lead to quick disease response, but how it can best be incorporated early into multi-modality treatment in the urgent clinical setting is often unclear.MethodsHere, we outline a practical approach to planning and incorporating urgent RT in patients with hematologic malignancies involving the CNS. We provide a review of the literature to inform RT indications, timing, dosing, and treatment volumes by histology and clinical scenario. We also highlight evolving controversies in this field and growing indications for RT in conjunction with novel therapeutics.ResultsRT is often the quickest-acting, most reliable tool to salvage cranial neuropathies or neurologic deficits and should be considered early. If systemic or intrathecal therapy are expected to achieve swift response as upfront treatment, simulation should still be planned in the event that response is delayed and RT is needed. RT in combination with certain systemic or intrathecal therapies can lead to unacceptable neurotoxicity; therefore, early multidisciplinary discussion to appropriately sequence therapies is critical. Thorough work-up with systemic imaging, complete neuroaxis MRI, ophthalmologic exam, and cerebrospinal fluid sampling can dictate target volumes from focal RT to comprehensive craniospinal irradiation (CSI). Dosing can range from as low as 4 Gray (Gy) for indolent disease to 36-50 Gy for more aggressive or refractory disease. Often, mid-treatment re-planning can be considered to address swift volume reduction to improve the therapeutic window. RT plays a promising role for bridging symptomatic patients to novel therapeutics (e.g., chimeric antigen receptor T-cell therapy), but optimal dosing and treatment volumes are evolving topics that require further prospective evaluation.ConclusionsRT is a powerful tool for achieving rapid responses in hematologic malignancies and therefore should be considered early in urgent neurologic settings. Thorough workup and discussions with the multi-disciplinary team are critical to best incorporate RT in the context of other CNS-penetrating therapies. Further work is warranted on defining RT target volumes in the context of novel therapeutics.